You are on page 1of 1

1 ‫ ﺒﻛﺎﻟورﻴﺎ ﻋﻠوم ﻓﻴزﻴﺎﺌﻴﺔ‬2 ‫ﺜﺎﻨوﻴﺔ ﺒﺌر أﻨزران ـ ﺼﻔرو ـ‬

‫ ﺘوﻓﻴق ﺒﻨﻌﻤرو‬:‫ذ‬
@ÄrÄ›ÄrÄ·Ä‹a@lbÄèÄzÄ‹a 2012 – 2011

sin( x + 2kπ ) =
sin( x) sin 2 x + cos 2 x =
1
sin(− x) = − sin( x) sin(π + x) =
− sin( x) sin(π − x) =sin( x) tan 2 x
cos( x + 2kπ ) =
cos( x) sin 2 x =
cos(− x) = cos( x) cos(π + x) =− cos( x) cos(π − x) =− cos( x) 1 + tan 2 x
tan( x + kπ ) =
tan( x)
tan( − x) =− tan( x) tan(π + x) =tan( x) tan(π − x) =− tan( x) 1
k ∈ cos 2 x =
1 + tan 2 x

π π
( + x) ( − x)
(sin x =sin a ) ⇔ ( x ∈ {a + 2kπ / k ∈ } ∪ {π − a + 2kπ / k ∈ }) 2 • •2 π π
sin( − x) =
cos( x) sin( + x) =
cos( x)
(cos x =cos a ) ⇔ ( x ∈ {a + 2kπ / k ∈ } ∪ {− a + 2kπ / k ∈ }) 2 2
(π − x)• •x
=
(tan x tan a) ⇔ x ∈ {a + kπ / k ∈ } π π
cos( − x) =
sin( x) cos( + x) =
− sin( x)
@ 2 2
a 2t 1− t2 2t π 1 π 1
t tan( = ) : sin a = cos a = tan a (π + x)• • −x tan( − x) = tan( + x) =

2 1+ t 2
1+ t2 1− t2 2 tan( x) 2 tan( x)

sin(a= + b) sin a cos b + cos a sin b a+b a−b
sin 2a = 2sin a cos a sin a + sin b =
2sin( )cos( )
sin(a= − b) sin a cos b − cos a sin b 2 2 1
= 2a cos 2 a − sin 2 a sin a =
sin b (cos( a − b) − cos( a + b))
cos cos(=a + b) cos a cos b − sin a sin b a+b a−b 2
sin a − sin b =
2cos( )sin( )
=
cos 2a 2cos 2 a − 1 cos(=a − b) cos a cos b + sin a sin b 2 2 1
=
sin a cos b (sin( a + b) + sin( a − b))
cos 2a = 1 − 2sin 2 a tan a + tan b a+b a−b 2
tan( a + b) = cos a + cos b =2cos( )cos( )
1 − tan a tan b 2 2 1
tan 2a =
2 tan a =
cos a cos b (cos( a + b) + cos( a − b))
tan a − tan b a+b a−b 2
1 − tan 2 a tan( a − b) = cos a − cos b =−2sin( )sin( )
1 + tan a tan b 2 2

÷ÄÄÔÄÄ–ÌÄÄnÄÄ‹bÄi

x deg 0 30 45 60 90 120 135 150 180 π
π π π π 2π 3π 5π 2 π
x rad 0 π 2π
6 4 3 2 3 4 6
3π 3
1
3 π
1 2 3 3 2 1 3/2
4
sin x 0 1 0 4
2 2 2 2 2 2
5π 2/2 π
3 2 1 1 2 3
cos x 1 0 − − − −1 6 1/ 2 6
2 2 2 2 2 2
1 1
tan x 0 1 3  − 3 −1 − 0
3 3
π 0
−1 3 2 1 1 2 3 1
− − −
sin ( x) = cos( x)
/
2 2 2 2 2 2
cos / ( x) = − sin( x) sin x sin( u ( x))
lim =1 lim =1
tan / ( x) = 1 + tan 2 ( x)
x→ 0 x u ( x)→ 0 u ( x)
5π −1/ 2 π
1 − cos x 1 1 − cos( u ( x)) 1 − −
lim = lim = 6 − 2/2
6
x→ 0 x2 2 u ( x)→ 0 ( u ( x)) 2 2 π
(sin( u ( x=
))) u ( x) ⋅ cos(u ( x))
/ /
3π −
lim
tan x
=1 tan( u ( x))
=1 − − 3/2 4
(cos( u ( x))) / =
−u / ( x) ⋅ sin( u ( x)) x→ 0
lim 4 π
x u ( x)→ 0 u ( x) 2π −1 −
( tan(u ( x)))=
/
u / ( x) ⋅ (1 + tan 2 (u ( x))) − π 3
3 −
2